Operations Management - Tran, Cong Thanh (Khoa Quốc tế, ĐHQGHN, 2020)
At the end of the course, students will have a fair understanding of the role Operations Management plays in business processes, as well as all aspects of the process of transforming inputs into outputs of finished goods or services. Specifically: Understand the aim and scope of operations management, and the role of operations management in both production and non-production organizations, To explain the role of operations and production, and their interaction with the other areas of a firm: finance, marketing, organization, corporate governance, etc., To analyze operation processes from various perspectives such as efficiency, responsiveness, quality and productivity, Learn basic but useful analytical skills and tools in studying operations in specific and other activities, Understand the structure and processes of production and the management tools of planning, analyzing and developing them , Formulate the business solutions to manage the value creating processes efficiently, Relate major ideas of the operations management to current business cases